Educational Program of Nurses Practices Towards to Phototherapy at Neonatal Care Units - Laith Nawfal Bura’a, Nasir Muwfaq Younis (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of the study to identify the educational program of nurses Practices towards to phototherapy at neonatal care units. Material: Purposive sampling with no probability. Between the beginning of January 2023 and the beginning of February 2023, a sample was taken. The nurses working in Mosul’s neonatal units were the ones who provided the sample. There were a total of (62) participants in the study, including (50) men and (12) women. The performance was divided into two sections: The first section dealt with the demographics of nurses. The second section dealt with the use of phototherapy by nurses in neonatal units. Results: The discovery revealed a substantial majority of them were males within the range of (80.65%), while women were (19.35%), and the average gender was (1.21), indicating that they were predominately male. The sample included in the study had the following ages: (30.43). Conclusion: This study concluded through the program that the nurses in the study sample before starting the program did not have any information related to the practical aspect of phototherapy, but when giving the program and after the second test, the results were clearly shown, there are very significant significant differences Keywords: Educational Program, Practices, Phototherapy, Neonatal Care Units.